The Influence of Human Relations, Work Facilities and Compensation on Employee Job Satisfaction - Aulia, Jihan Permata; Deni, Asep; Setiadi, Sandi (Jurnal Ilmiah Sumber Daya Manusia, 2025)
This study was conducted to determine how much influence Human Relations, Work Facilities, and Compensation have on employee job satisfaction at the Sukabumi City Public Works and Spatial Planning Agency. The research method used is the associative quantitative method. The population in this study was 235 employees with a sample size of 70 people. The type of data used is primary data by distributing questionnaires to respondents. The analysis method used is the validity and reliability test. The prerequisite analysis test includes data normality test, linearity test, heteroscedasticity test and multicollinearity test. The analysis technique used is multiple linear regression. The partial results of the human relations variable are proven by the results of the t-test showing that human relations have a positive and significant effect on job satisfaction, on the work facilities variable is proven by the results of the t-test showing that work facilities have a positive and significant effect on job satisfaction, on the compensation variable is proven by the results of the t-test showing that compensation has a positive and significant effect on job satisfaction. In addition, the results of the study of human relations, work facilities and compensation simultaneously have a positive and significant effect on job satisfaction at the Sukabumi City Public Works and Spatial Planning Agency. This should be a concern for the Sukabumi City Public Works and Spatial Planning Department to pay more attention to the conditions and comfort of its employees, improve the quality and availability of facilities, and pay attention to the welfare of its employees.